2019
DOI: 10.1016/j.jid.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Skin of Color: Disruption to Elastic Fiber Organization Is Detrimental to Skin’s Biomechanical Function

Abstract: Skin aging is a complex process involving the additive effects of time-dependent intrinsic aging and changes elicited via skin's interaction with the environment. Maintaining optimal skin function is essential for healthy aging across global populations; yet most research focuses on lightly pigmented skin (Fitzpatrick phototypes IeIII), with little emphasis on skin of color (Fitzpatrick phototypes VeVI). Here, we explore the biomechanical and histologic consequences of aging in black African-American volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 56 publications
0
38
1
2
Order By: Relevance
“…Furthermore, skin may be at higher risk of damage because of age-related changes. 126 Risk assessment should focus on the body site onto which the device has been or will be applied. However, patients with oedema or lymphoedema may be at risk, despite having skin that is generally in good condition.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Furthermore, skin may be at higher risk of damage because of age-related changes. 126 Risk assessment should focus on the body site onto which the device has been or will be applied. However, patients with oedema or lymphoedema may be at risk, despite having skin that is generally in good condition.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…In this study, Langton et al (2019) utilized a Cutometer to assess the effects of aging on the biomechanical properties of skin of color. Two groups of African American patientsyoung (23.9 AE 3.6 years) and aged (70.8 AE 5.9 years)participated in the study.…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…These results are consistent with those of previous studies (Boyer et al, 2009;Cua et al, 1990) that demonstrated worsening elasticity in older adults. Langton et al (2019) propose that the dermal-epidermal junction (DEJ) flattening and the changes in dermal elastic fiber organization that occur with age could contribute to loss in elasticity, as they result in a weakened dermal-epidermal interface and an epidermis that is less resistant to shearing forces (Lavker et al, 1987).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
See 2 more Smart Citations